Rhythmical patterns of quartz-molybdenite and interpretation of its origin - O. B. Azovskova (Литосфера, 2016)
Subject of the study was molybdenite aggregate (0.9 × 0.5 cm) in granite from Cu ± Mo-porphyry mineralisation (Altynai Massif, eastern part of Middle Urals). Microprobe analysis and electron microscopy identified fine alternating microlayers of molybdenite and quartz in all 0.4-5.0 mm flakes of molybdenite. Thickness of normally discontinuous layers of quartz is 0.5-3 μ, distance between layers - 8-100 μ or more. Quartz layers are aligned only with the basal cleavage of molybdenite. In some molybdenite flakes or parts of flakes quartz layers are absent or very few in number. Large flakes of molybdenite are surrounded by fine-grained aggregate of quartz, chamosite and molybdenite. Occasional grains of fluorite and galena have also been found within this aggregate. Molybdenite flakes in such areas contain no quartz layers, have random orientation, and can be seen as fragments cemented by chamosite and quartz. Molybdenite has consistently low rhenium content of 29 ppm (according to ICP-MS). It is suggested that molybdenite-quartz rhythms are likely to correspond to primary oscillatory distribution which was subsequently subjected to deformations and redistribution of silica in crushed areas.